RESISTENCIA A LA FRACTURA RADICULAR ANTE FUERZAS COMPRESIVAS DE DIENTES TRATADOS ENDODÓNTICAMENTE Y RESTAURADOS CON TRES TÉCNICAS DE COMPLEMENTACIÓN (2010)
Objective: To establish a difference in the resistance to the fracture of teeth restored with casting gold post, glass fiber post and the system of coronal complementation.Methods: An experimental In vitro study was done. Forty-five upper first premolars were selected and divided in three equal groups: gold type III post, glass fiber post and the system of coronal complementation. Each tooth was treated endodontically; coronal cuts were made and were put in acrylic resin cubes with a matrix of aluminum. The three groups were prepared coronally in 360 degrees and cement a metal cap base (remanium) calibrated 0.5 microns. Finally, subjected to compressive force on the Shimatzu universal machine with an initial load of 200 newtons at a constant speed of 0.05 mm/min and the application of force at the time was retired graphically showed the collapse of the translated curve fails.Results: Twenty nine percent of teeth with gold post presented fracture, half of this fracture was at medium level and the others were at coronal and apical level. In the group with the system of coronal complementation only one premolar presented fracture at the medium level (7%). Statistical significant dependence was established between the technique of complementation and resistance to fracture and the fracture level (p < 0,05).Conclusions: Restored teeth with casting posts had better resistance to force but had a higher probability to fracture. Restored teeth with fiber glass post presented less resistance to force but did not present any fracture. Restored teeth with the system of coronal complementation presented less resistance to fracture and according to the level of fracture it was in a better level.